The perception of organizations by the Y Generation - Perrone, Cláudia Maria; Engelman, Selda; Santos, Anelise Schaurich; Sobrosa, Gênesis Marimar Rodrigues (Revista de Administração da UFSM, 2013)
Nowadays the called Y Generation is perceived as a challenge for organizations and their managers. Among the authors of this theme there is a convergence of views on the intense relationship that these young people have with the technologies. This is the determinative trait for the understanding of unique characteristics of Y Generation. The objective of this study was investigated what are the organizational aspects that attract the Y Generation, as well as what they expect from a company. For this reason, data were obtained from 10 young people belonging to this generation. They answered a instrument that contained open questions. The data were analyzed by categorical thematic content analysis. The results indicate that youth of Y Generation experience a hybrid situation in organizations, because they want a organization post-industrial and live in organizations with aspects taylor-fordist. They oscillate between adaptation and appropriation of competence as self-confidence and eagerness for knowledge, maintaining as value the process of self-construction, that should not be simplified to an identity presupposed by the company and a reduced capacity for action before this perspective problem.